A MODEL FOR DIALOGICAL COMPETENCE FOR DEVELOPMENT OF THE CONTEMPORARY PROFESSIONAL AND ORGANIZATION - Kamenova, D.; Georgieva, ZH. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
The report presents an innovative model for dialogue created specifically to help managers acquire the necessary competence. In a time where the business environment is constantly changing and the bargaining chip I information the knowledge and skills for dialogue is becoming a crucial factor for the success of every organization. The presented model for dialogic competence creates an opportunity for a educational standard for the contemporary professionals in management. The standard as a system for knowledge and skills can be also used in the education of every type of professionals in the dialogic aspect. The model is opening opportunities for further research of the types of contemporary organizations depending on the dialogical competence of the associates in the organization. This would probably reveal that the massive amount of information is not enough for the prosperity of the contemporary professionals and organizations